Brincar na vida e na docência: trajetórias de formadoras(es) brincantes - Rosa, Alessandra de Campos e Silva (2020)
The research developed in the Master's Program in Education, in line 1 - Teacher training and educational practices, aims to present and discuss experiences of the teachers who play in the formation of teachers of kindergarten. Specifically, understanding the pathways that constituted playing teachers and how playing is articulated with their educational practices. The narrative research used the qualitative methodology, firstly performing a bibliographic review about playing, childhood and the formation of teachers, having as theoretical support scholars such as Kishimoto (2010, 2014, 2007, 2005), Sarmento (2005, 2002, 2007, 2004, 2008), Faria (2011), Brougère (1989, 1997), Abramowicz (2010), Santos (2010, 2012), among others. As a technical device, it sought the episodic interview supported by the authors Flick (2002), Schütze (2010, 2002), Jochelovitch and Bauer (2010) among others. The narratives shared by the collaborators were analyzed in order to make meaningful connections between their playing experiences and the formation of preschool teachers, revealing their knowledge and practices and how they constituted playful trainers. . Through the analysis of the reports we can infer that the playing teachers have trajectories, knowledge and practices that connect and allow establishing relationships revealing their unique experiences and the appreciation of play and play as the axis of the formative work they develop.